It’s Time to Relax: The Critical Importance of Digital Mental Health Products in the Context of Surveillance Capitalism - Sena Partal; Sasha Smirnova (Temes de Disseny)
There has been a huge increase in the use of digital technology throughout healthcare in recent years, with everything from apps to wearable tech. The mental health and wellbeing sector has been no exception. There are a wide variety of digital mental health apps available directly from app stores, making therapeutic techniques accessible for every smartphone user.